Proteomic and cellular localisation studies suggest non‐tight junction cytoplasmic and nuclear roles for occludin in astrocytes. (30th May 2018) - Morgan, Sarah V.; Garwood, Claire J.; Jennings, Luke; Simpson, Julie E.; Castelli, Lydia M.; Heath, Paul R.; Mihaylov, Simeon R.; Vaquéz‐Villaseñor, Irina; Minshull, Thomas C.; Ince, Paul G.; Dickman, Mark J.; Hautbergue, Guillaume M.; et al.
Abstract: Occludin is a component of tight junctions, which are essential structural components of the blood–brain barrier. However, occludin is expressed in cells without tight junctions, implying additional functions. We determined the expression and localisation of occludin in astrocytes in cell culture and in human brain tissue, and sought novel binding partners using a proteomic approach. Expression was investigated by immunocytochemistry and immunoblotting in the 1321N1 astrocytoma cell line and ScienCell human primary astrocytes, and by immunohistochemistry in human autopsy brain tissue. Recombinant N‐ and C‐terminal occludin was used to pull‐down proteins from 1321N1 cell lysates and protein‐binding partners identified by mass spectrometry analysis. Occludin was expressed in both the cytoplasm and nucleus of astrocytes in vitro and in vivo. Mass spectrometry identified binding to nuclear and cytoplasmic proteins, particularly those related to RNA metabolism and nuclear function. Occludin is expressed in several subcellular compartments of brain cell‐types that do not form tight junctions and the expression patterns in cell culture reflect those in human brain tissue, indicating they are suitable model systems. Proteomic analysis suggests that occludin has novel functions in neuroepithelial cells that are unrelated to tight junction formation. Further research will establish the roles of these functions in both cellular physiology and in disease states. Abstract : In this paper, we demonstrate that occludin is expressed in both the cytoplasm and nucleus of human astrocytes and using mass spectrometry novel occludin binding partners were identified. These candidate protein‐binding partners suggest a potential role of occludin in RNA metabolism and nuclear functions.